The influence of policy and competitiveness on service quality and its implications on customer satisfaction for foreign ship agency approval at the Directorate of Sea Traffic and Transport - Sofyan, Nadiah; Saragih, Robensius; Malau, April Gunawan; Susilo, Wilhelmus Hary (Dinasti International Journal of Management Science, 2026)
This research analyzes the influence of policy and competitiveness on service quality and its implications on customer satisfaction related to the Foreign Ship Agency Approval at the Directorate of Sea Traffic and Transport. The sea transportation sector plays an important role in Indonesia's international trade, with nearly 90% of the trade volume conducted by sea. The Foreign Ship Agency Approval Service is the initial entry point for foreign ships into Indonesian waters which has undergone digital transformation through the Sea Transportation Traffic Management Information System since 2016. This quantitative research involved 92 customer respondents who were selected using a simple random sampling technique. Data analysis using Structural Equation Modeling with the help of SmartPLS showed that policy had a significant influence on service quality by 64.4% and competitiveness contributed by 28.9%. Service quality has proven to be a full mediator in policy relations and competitiveness to customer satisfaction with the strongest contribution of 75.6%. The dimensions of policy compliance, technology infrastructure, service reliability, and information accessibility are the dominant factors that affect customer satisfaction. The findings of the research show the importance of improving service reliability and information technology integration between agencies to improve the efficiency of coordinating foreign ship agency approval services.